GIS Shell Vibration Mechanism and Partial Discharge Optimization Diagnosis - Li ZHANG; Bin QU; Yongning WANG; Rong CHEN; Baowen LIU; Shaojie ZHANG; Bin HAN; Hongzhong MA (Zhongguo dianli)
In order to explore the mechanism of abnormal vibration of power equipment caused by electromagnetic induced vibration and partial discharge (PD) in GIS, the distribution model of induced eddy current and its electromagnetic force considering skin effect in GIS was established, and the development experiment of PD at metal tip of GIS was set up. The pulse current and the vibration signal of GIS shell are measured simultaneously when GIS PD occurs, and the vibration characteristics and mechanism of GIS PD are explored by integrating the electromechanical signal. It is found that there are obvious differences between electromagnetic induced vibration and PD induced vibration of GIS shell. The frequency of PD induced vibration of GIS shell is the same as that of pulse interval frequency, and the energy is concentrated at the frequency of 50Hz. Finally, the SVM model optimized by particle swarm optimization (PSO) is constructed to realize the pattern recognition of different discharge levels, and it is applied in practice.